INFLECTIONAL AND DERIVATIONAL MORPHEME IN THE CONVERSATION’S ARTICLE - Adinda Putri Maharani; Dewi Nurmala (PHILOLOGY Journal of English Language and Literature, 2026)
This study analyzes Inflectional and Derivational morphemes in The Conversation's article. Using a qualitative content analysis method with a theoretical approach. The results of the study show that there are 305 Inflectional Morphemes with the most dominant being Plural, while Derivational morphemes are 83 with the most dominant being the Adjective form into Adverb. This study provides a new perspective on the development of Inflectional and Derivational morphemes found in an article.